Онтологічна характеристика обшуку як слідчої (розшукової) дії - Левін, В. І.; Levin, V. I. (Вісник Луганського державного університету внутрішніх справ ім. Е. О. Дідоренка. – 2017. – № 4 (80). – С. 88-96, 2017)
У статті наведено наукові позиції вчених щодо тлумачення поняття слідчої (розшукової) дії, а також обшуку як одного з видів слідчої (розшукової) дії. Підтримано наукове бачення щодо доцільності класифікації обшуку залежно від об’єкта його проведення. Виснувано, що обшук має примусовий та пошуковий характер, тому його проведення пов’язано з обмеженням певних прав, свобод і законних інтересів громадян, через що вимагає дотримання встановлених законом гарантій.

The scientific positions of scientists concerning the interpretation of the concept of investigative (investigative) action, as well as the search as one of the types of investigative (investigative) action are presented in the article. The scientific vision of the expediency of classification of the search depending on the object of its conduct is supported: 1) search of housing (that is, a premise that is in permanent or temporary possession of a person, regardless of its purpose and legal status, and adapted for the permanent or temporary residence of individuals in it, as well as all the components of such premises); 2) search of another person's property: vehicles, land (garden, garden, yard, forest plots, fields); garages, other buildings or premises for domestic, official, economic, industrial and other purposes that are in the possession of the person; 3) search of the person (personal search). It is determined that the search is conducted for a specific purpose in the presence of legal and factual bases. The conducted study made it possible to draw the following conclusions: 1) the search refers to forced investigative (search) actions; 2) has a search character, while the search objects are specified in the order of the investigator of the judge; 3) the search is related to certain violations of the rights, freedoms and legitimate interests of citizens, in particular the inviolability of the person, the dwelling, and therefore requires compliance with the guarantees provided by law. The term "search" should be understood as an investigative (wanted) action conducted on the basis of an investigating judge's decree and is a compulsory survey of premises, terrain, individuals in order to identify and record information about the circumstances of the commission of a criminal offense, a criminal offense instrument or property that was obtained as a result of his commission, as well as the location of wanted persons.

В статье приведены научные позиции ученых относительно толкования понятия следственной (розыскной) действия, а также обыска как одного из видов следственной (розыскной) действия. Поддержано научное видение целесообразности классификации обыска в зависимости от объекта его проведения.
The Ontological Characteristic of Search as an Investigative (Searching) Action
Онтологическая характеристика обыска как следственного (розыскного) действия
Левін, В. І. Онтологічна характеристика обшуку як слідчої (розшукової) дії / В. І. Левін // Вісник Луганського державного університету внутрішніх справ ім. Е. О. Дідоренка. – 2017. – № 4 (80). – С. 88-96.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; слідча (розшукова) дія; investigative (research) action; следственное (розыскное) действие; обшук; search; обыск; погляди вчених; views of scientists; взгляды ученых